Radiation protection in endoscopy - Tchekmedyian, Asadur J. (2023)
Endoscopy has evolved from a purely diagnostic technique to a therapeutic procedure. This is possible in many cases thanks to the use of fluoroscopy, which entails exposure to ionizing radiation for both patients and the personnel involved. Endoscopic retrograde cholangiopancreatography (ERCP), which necessarily requires fluoroscopy, is classified by the Food and Drug Administration as an examination with a potential risk of triggering radiation induced injuries. This article reviews the biological effects of radiation, the types of radiological equipment used in ERCP, as well as the magnitudes and dosimetric units, to finally address the radio protection elements in the endoscopy room. The objective is to provide the reader with the information to be able to perform these procedures with the greatest radiological safety for both patients and occupationally exposed personnel.